Fungal Gene Mutation Analysis Elucidating Photoselective Enhancement of UV-C Disinfection Efficiency Toward Spoilage Agents on Fruit Surface - Zhu, Pinkuan; Li, Qianwen; Azad, Sepideh M.; Qi, Yu; Wang, Yiwen; Jiang, Yina; Xu, Ling (Frontiers in Microbiology, 2018)
Short-wave ultraviolet (UV-C) treatment represents a potent, clean and safe substitute to chemical sanitizers for fresh fruit preservation. However, the dosage requirement for microbial disinfection may have negative effects on fruit quality. In this study, UV-C was found to be more efficient in killing spores of Botrytis cinerea in dark and red light conditions when compared to white and blue light. Loss of the blue light receptor gene Bcwcl1, a homolog of wc-1 in Neurospora crassa, led to hypersensitivity to UV-C in all light conditions tested. The expression of Bcuve1 and Bcphr1, which encode UV-damage endonuclease and photolyase, respectively, were strongly induced by white and blue light in a Bcwcl1-dependent manner. Gene mutation analyses of Bcuve1 and Bcphr1 indicated that they synergistically contribute to survival after UV-C treatment. In vivo assays showed that UV-C (1.0 kJ/m2) abolished decay in drop-inoculated fruit only if the UV-C treatment was followed by a dark period or red light, while in contrast, typical decay appeared on UV-C irradiated fruits exposed to white or blue light. In summary, blue light enhances UV-C resistance in B. cinerea by inducing expression of the UV damage repair-related enzymes, while the efficiency of UV-C application for fruit surface disinfection can be enhanced in dark or red light conditions; these principles seem to be well conserved among postharvest fungal pathogens.